Clinical Profile of End Stage Renal Disease Patients Undergoing Hemodialysis in a Tertiary Care Hospital of Nepal - Mandal, Rajesh Kumar; Pande, Rajan; Yadav, Krishna Kumar; Goit, Kuldip (Journal of Advances in Internal Medicine, 2023)
BACKGROUND Maintenance hemodialysis is a popular treatment modality of renal replacement therapy for end stage renal disease patients. The clinical profile of end-stage renal disease (ESRD) and dialysis in Mid Western Nepal are scarce. This study aimed to study the clinical profile of ESRD patients undergoing hemodialysis at the tertiary care Hospital. METHODS This study was a single center based cross sectional observational study carried out over a period from 15th December 2022 to 15th February 2023 in Department of Medicine. A total of 40 patients undergoing maintenance hemodialysis were enrolled in the study. Data about Socio demographic profiles , clinical data, duration of chronic kidney disease (CKD), major comorbidity, the presumed etiology of ESRD, duration of haemodialysis, laboratory parameters including Renal function tests etc were entered in MS Excel and analyzed through SPSS 21. RESULTS A total of 40 patients were enrolled in the study. Males were 25(62.5%) and females were 15(37.5%). The mean age of the patient was 45.75±15.2 years. The most common cause of end stage renal disease and reasons for admission were hypertension nephropathy 36(90%) and Type 2 diabetes mellitus 9(22.5%) respectively. Anemia was the most common hematological findings in ESRD patients (>90%) followed by hypocalcemia in 65%. CONCLUSIONS Hypertensive nephropathy was the commonest cause for CKD followed by diabetic nephropathy and glomerulonephritis. Early detection and effective management of these illnesses can delay the onset, progression of CKD to end stage and subsequent morbidity and the requirement of renal replacement therapy.